1981
DOI: 10.1037/0096-1523.7.2.459
|View full text |Cite
|
Sign up to set email alerts
|

Subjective ratios and differences in perceived heaviness.

Abstract: In previous studies, judgments of ratios and differences in subjective magnitude have yielded similar orders, consistent with a hypothesis that a single perceived relation underlies both judgment tasks. In the present research, 15 subjects estimated heaviness differences between 28 pairs of eight weights and each of 8 groups of 10 subjects evaluated heaviness ratios of eight variable stimuli with respect to a different standard stimulus. Presenting stimuli that were equally spaced on a cube-root scale of weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
3

Year Published

1982
1982
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(74 citation statements)
references
References 11 publications
3
68
3
Order By: Relevance
“…It might be argued that Rule et al (1981) were correct in their domain (heaviness) when they assumed that J* was the same for all groups of subjects. However, it seems likely that if our Experiment 1 was replicated with lifted weights, similar contextual effects would occur in which the curves could be either made to fit the ratio model, give the same order as the subtractive model, or violate the ratio model depending on the response range and standard.…”
Section: Contextual Effects In Between-subject Versus Within-subject mentioning
confidence: 99%
See 2 more Smart Citations
“…It might be argued that Rule et al (1981) were correct in their domain (heaviness) when they assumed that J* was the same for all groups of subjects. However, it seems likely that if our Experiment 1 was replicated with lifted weights, similar contextual effects would occur in which the curves could be either made to fit the ratio model, give the same order as the subtractive model, or violate the ratio model depending on the response range and standard.…”
Section: Contextual Effects In Between-subject Versus Within-subject mentioning
confidence: 99%
“…In a recent paper that examined "ratio" and "difference" judgments, different groups of subjects used different standards for the "ratio" task (Rule, Curtis, & Mullin, 1981). They assumed that such "ratio" judgments can be described by the following ratio model:…”
Section: Contextual Effects In Between-subject Versus Within-subject mentioning
confidence: 99%
See 1 more Smart Citation
“…Rule, Curtis, and their colleagues (e.g., Rule & Curtis, 1980, 1982Rule, Curtis, & Mullin, 1981) argued that subjects are able to judge either differences or ratios when instructed to do so. According to these authors, category ratings are linear with subjective intensity, and magnitude-estimation instructions induce a response output function that has the form of a power function.…”
Section: -10 Omentioning
confidence: 99%
“…If the subtractive model is assumed, then Figure 6 indicates that pitch is a log function of frequency. Figure 6 provides a direct test of an idea suggested by Rule, Curtis, and Mullin (1981) as an explanation of the monotonic relationship between "ratios" and "differences." Rule et al suggested that "ratio" scale values for the first stimulus (standard) would show regression to the mean, but "difference" scale values would not.…”
Section: Subjectsmentioning
confidence: 99%